Application of Storytelling as an Effort to Improve Child Visits in Yosemite Village RW 03 Read Sukun Malang - Asri, Tri Mega; Puspitasari, Anissa (Record and Library Journal, 2018)
Background of the study: The application of storytellingPurpose: This study aims to determine the level of the child's visit after the application of storytelling in the park read RW 3 Breadfruit Malang.Method: In the application of this storytelling, researchers divided into four cycles. Each cycle using a different media story that is stuffed hilt, drawing on HVS, the image of the picture book and flannel board. Different stories read at each meeting, but the story is still in one kind, IE fables (Fiction animal life that behaves like a human), Stages of story telling is done is the planning, implementation, observation, and reflection.Findings: Based on the research results, in the first cycle the final conditions are 6 children were keen to come back, in the second cycle increased to 34 children. However, in Cycle III, participants storytelling began to decline, the overall number of participants in Cycle III is 28 children, and in Cycle IV decreased again to 21 children.Conclusion: Children have decreased interest in returning, so the methods used should be more optimized.